PERANCANGAN MESIN PENCACAH SAMPAH ORGANIK DENGAN MENGGUNAKAN TIPE MATA PISAU HAMMER - Sthiefandy, Alvin; Munaiseche, Robert O.K; Pomalingo, Moh. Fikri (Steam Engineering, 2024)
According to the national waste management information system (SIPSN) in 2021 organic waste in Manado city is 47.7%. The purpose of this research is to reduce organic waste in the tondano market and get a hammer blade design on the chopping machine, this research uses an experimental method which includes design, data collection, making initial design concepts, selecting materials, making 2d and 3d designs, manufacturing processes, testing tools, reports. The organic waste chopping machine works mechanically using diesel rotating speed of 2600 rpm, the working principle of the chopping machine is to enter organic waste through the hopper then the waste is chopped with a rotating hammer blade totaling 6 and 2 silent hammer blades. Waste will be filtered into smaller pieces and easily processed further, such as maggot food, compost or organic fertilizer. From the results of the research conducted and based on data processing, it can be concluded that this waste chopping machine has been successfully made and fulfills the first goal of the researcher to reduce the amount of waste in the Tondano market whose volume is 300kg / day. The machine is able to chop organic waste into fine pulp with a waste chopping capacity of 553.84 kg / hour.